Optimasi Suhu dan Waktu Deasetilasi Kitin Berbasis Selongsong Maggot (Hermetia ilucens) Menjadi Kitosan - Sri Wahyuni; Ranti Selvina; Ridha Fauziyah; Haryo Tejo Prakoso; Priyono Priyono; Siswanto Siswanto (Institut Pertanian Bogor, 2020)
As Black Soldier Fly farming has become an emerging trend in Indonesia there is a new opportunity to take advantage from the waste generated from the activity. One of them is the exuviae, which is resulted from the emergence of the fly and it has a high chitin content. Chitin from BSF exuviae have low Cristalinity Indexes. Hence, it shows a promising potential to be processed to produce a new biopolimer. Therefore, converting chitin from BSF exuviae into chitosan using deacetylation process was studied. The researched variables were temperature and the duration of the process, which were studied at 50, 60, 70, and 80°C for 12 hours and 8, 10, 12, and 14 hours at 60°C, respectively. Chitosan produced in the temperature of 60, 70, and 80°C has met the standard quality, and the best duration of deacetylation process was 8 hours. The solubility test in acetic acid (2%) showed that chitosan solubility was increased with the increase of temperature, while it decreased as the duration of the process becomes longer. Moreover, the degree of deacetylation showed that chitosan was produced with the best quality in 80°C of temperature (75.98%) and 8 hours of deacetylation process (71.12%). Keywords: chitosan, degrees of deacetylation, exuviae of black soldier fly